PENGARUH GOOD CORPORATE GOVERNANCE DAN FIRM SIZE TERHADAP PROFITABILITAS - Lestari, Sri Indah; Dewi, Siska; Safitri, Anni; Sholikah, Mar”™atus (Politeknik Negeri Semarang, 2024)
This study aims to analyze the influence of the board of commissioners, audit committee, independent commissioners, institutional ownership, board of directors, and company size on the profitability of banking financial companies listed on the Indonesia Stock Exchange (IDX) in the 2019-2022 period. The research sample comes from banking companies listed on the IDX during the 2019-2022 period. The datacollection technique in this study used a purposive sampling technique.The data were obtained from publicly available financial company reports with a population of 12 banking companies according to the criteria. Basedon the results of hypothesis testing it was found that the board ofcommissioners and ownership of financial companies have an influence on company performance, while the audit committee, independent commissioners, board of directors, and company size have no influence onfinancial company performance.